The Impact of Parental Involvement on Early Childhood Development: A Case Study - Ayu Fajarwati; Eka Setiawati; Yusdiana (CV Kalimasada Group, 2025)
The purpose of this study was to analyze the impact of parental involvement on early childhood development through a case study on a group of children in one of the early childhood education institutions. This study uses a qualitative approach with a case study method, where data is obtained through observation, in-depth interviews, and documentation. The results showed that active involvement of parents, both in educational, emotional, and social aspects, has a significant influence on cognitive development, language, motor, and character of children. Factors such as frequency of interaction, quality of communication, and emotional support have been shown to contribute positively in shaping children's behavior and abilities. These findings confirm the importance of collaboration between parents and educators in creating an environment that supports optimal child development.